Impact of nutrition counseling on anthropometry and dietary intake of multiple sclerosis patients at Kasr Alainy Multiple Sclerosis Unit, Cairo, Egypt 2019-2020: randomized controlled clinical trial - Zeinab Afifi; Amr Hassan; Nebal Abdelrahman; Asmaa El Sayed; Marwa Salem (BMC, 2023)
Abstract Background Faulty dietary habits and overnutrition are prevalent among Egyptian patients with multiple sclerosis (MS) who do not receive nutrition care as part of treatment. Thus, this study was conducted to identify the effect of nutrition counseling on the nutritional status of patients with MS. This endeavor might provide evidence for the value of counseling in such a setting and advance the integration of nutrition counseling into the routine management of patients with MS. Methods A single-blinded, parallel-randomized controlled clinical trial was conducted at Kasr Alainy MS Unit on 120 eligible patients with MS from September 2019 to February 2020. Patients were randomly allocated to either the nutrition counseling intervention group (IG) or the control group (CG). Allocation concealment was performed by using sequentially numbered opaque sealed envelopes. All patients were assessed initially and complied with the Kasr Alainy MS Unit standard management protocol for the study period. Only patients in the IG underwent initial nutrition counseling sessions followed by a monthly evaluation. All patients were assessed at the end of the 3-month follow-up period. Sociodemographic data were gathered through a structured interview. Nutritional status was assessed anthropometrically and via 24-h recall. The 2 groups were compared initially and at the end of the follow-up. Both intention-to-treat and per-protocol analyses were conducted. Results At baseline assessment, the prevalence of overweight and obesity was 31.7% and 32.5%, respectively, and the mean body mass index was 27.7 ± 5.7 kg/m2. Mean waist circumference was 93.5 ± 11.9 and 99.2 ± 13.1 cm for males and females, respectively. Approximately 27.3% of males and 83.9% of females showed abdominal obesity. After 3 months of counseling, weight, body mass index, waist circumference, nutrient intake and adequacy significantly improved in the IG (p < 0.05). Conclusion Nutrition counseling significantly improved anthropometric measurements, dietary habits, nutrient intake and adequacy. Trial registration The study was registered on ClinicalTrial.gov and was given a code (NCT04217564).